2011
DOI: 10.1136/bmjqs.2009.032326
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a preoperative team briefing: a new communication routine results in improved clinical practice

Abstract: BACKGROUND Suboptimal communication within healthcare teams can lead to adverse patient outcomes. Team briefings were previously associated with improved communication patterns, and we assessed the impact of briefings on clinical practice. To quantify the impact of the preoperative team briefing on direct patient care, we studied the timing of preoperative antibiotic administration as compared to accepted treatment guidelines. STUDY DESIGN A retrospective pre-intervention/post-intervention study design assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
57
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(59 citation statements)
references
References 38 publications
1
57
0
1
Order By: Relevance
“…Evidence for the effectiveness of the SSC in reducing patient morbidity and mortality is generally very positive31 32 and the three phases of the SSC: sign in, time out and sign out are well established in many hospitals. More recently, the Patient Safety First Campaign in the UK recommended that preoperative briefings and postoperative debriefings should be included in the SSC to form the Five Steps to Safer Surgery (5SSS),33 to further improve communication between the OR team 34 35. Hill and colleagues also found significant improvements in safety culture attitudes after the implementation of the 5SSS, specifically highlighting the importance that the OR staff attached to the formal prelist briefings 36.…”
mentioning
confidence: 99%
“…Evidence for the effectiveness of the SSC in reducing patient morbidity and mortality is generally very positive31 32 and the three phases of the SSC: sign in, time out and sign out are well established in many hospitals. More recently, the Patient Safety First Campaign in the UK recommended that preoperative briefings and postoperative debriefings should be included in the SSC to form the Five Steps to Safer Surgery (5SSS),33 to further improve communication between the OR team 34 35. Hill and colleagues also found significant improvements in safety culture attitudes after the implementation of the 5SSS, specifically highlighting the importance that the OR staff attached to the formal prelist briefings 36.…”
mentioning
confidence: 99%
“…[9][10][11][12]17 Briefing and conducting the surgical time-out were included in the descriptive anchors, as they represent formal strategies to ensure a shared understanding that have been associated with patient safety and are commonly carried out by residents. 3,35,36 The fourth item, communication, has equally been identified as a critical factor in intraoperative patient safety. 2 Similarly, communication failures have been associated with perioperative complications and errors.…”
Section: Article In Pressmentioning
confidence: 99%
“…Previous research has found that team membership and the quality of intergroup and interdisciplinary communications potentially can contribute to the quality of patient care. 11,18 LITERATURE REVIEW All surgical procedures require a high level of coordination between various individuals from different professional disciplines. 15 The complexity of a surgical procedure affects every aspect of team performance.…”
Section: Significance To Nursingmentioning
confidence: 99%